2021
DOI: 10.1042/cs20200468
|View full text |Cite
|
Sign up to set email alerts
|

Absence of interleukin-10 reduces progression of shiga toxin-induced hemolytic uremic syndrome

Abstract: Hemolytic Uremic Syndrome, a disease triggered by Shiga toxin (Stx), is characterized by hemolytic anemia, thrombocytopenia and renal failure. The inflammatory response mediated by neutrophils (PMN) and monocytes is essential to HUS onset. Still, the role of anti-inflammatory cytokines is less clear. The deficiency of IL-10, an anti-inflammatory cytokine, leads to severe pathology in bacterial infections but also to beneficial effects in models of sterile injury. The aim of this work was to analyze the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Based on this, IL-10 could be considered not only a protective factor that regulates inflammation but also a detrimental factor that contributes to pathological changes leading to end-stage kidney diseases (18). In the context of HUS, it has been recently reported that the absence of IL-10 limits kidney damage in an experimental model induced by Stx (50).…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, IL-10 could be considered not only a protective factor that regulates inflammation but also a detrimental factor that contributes to pathological changes leading to end-stage kidney diseases (18). In the context of HUS, it has been recently reported that the absence of IL-10 limits kidney damage in an experimental model induced by Stx (50).…”
Section: Discussionmentioning
confidence: 99%